Baking Soda as A Fixation of Remasol is an Effective Method for Colouring Batik to Be Combined eith Other Types of Colours - Karsam Karsam (Faculty of Civil Engeneering and Planning - ITATS, 2022)
Batik dyes are made from natural dyes and chemical dyes (rapid, indigosol, naptol, and remasol). Each batik dye requires a fixation material according to the type of colour used. Remasol colour (vinyl sulfone) is one type of reactive colour whose use is the most suitable to smear. Fixation of Remasol colour is using waterglass/sodium (Na2SiO3). Waterglass has a liquid nature, although it hardens easily after being exposed to the sun, it melts quickly when it contacts with water. Therefore, Remasol with waterglass fixation is not suitable when it is used with other colour combinations. For instance, it is combined with naptol. To produce a suitable combination, it is necessary to use baking soda [sodium bicarbonate (NaHCO3)] as a fixation of remasol. In this study, it is explained about the method of baking soda as a fixation of remasol as a baik dye combined with other types of colours. The result of this research is that baking soda as a fixation of remasol requires a ratio 1 : 1 (1 gram of baking soda : 1 gram of remasol). To produce a colour that matches the quidelines, after being applied, 72 hours of drying is required, after that it is blocked (covered with hot wax). This method can be used to colour batik with the dip dye technique which can be combined with naptol, rapid, and indigosol colours. The result of this study is expected to increase the number of colour variations in one sheet of cloth. For example, one sheet of cloth can use naptol, rapid, and indigosol. Because naptol, rapid, and indigosol have different colours, for example, naptol, rapid, and indigosol do not have turquoise blue. Turquoise only exists in remasol, and vise versa. The shortcoming in this research is that the experimental method carried out is still simple and has not used detailed laboratory test.